Hydrogel-based engineering of beige adipose tissue. Issue 40 (3rd July 2015) - Vaicik, M. K.; Morse, M.; Blagajcevic, A.; Rios, J.; Larson, J. C.; Yang, F.; Cohen, R. N.; Papavasiliou, G.; Brey, E. M.
Abstract : Brown and beige adipose tissues have a significant capacity for energy expenditure that may be exploited as a treatment for obesity and metabolic disease. Abstract : Brown and beige adipose tissues have a significant capacity for energy expenditure that may be exploited as a treatment for obesity and metabolic disease. However, the limited volumes of these tissues in adults hinders realization of this potential. Engineering beige adipose tissue may provide an alternative source of this tissue. In this paper we describe the preparation of poly(ethylene glycol) (PEGDA) hydrogels with mechanical properties similar to native adipose tissue. Adipose derived stem cells (ASC) were cultured in hydrogels without adhesive sequences or degradable monomers. Cells were able to differentiate, independent of scaffold properties and were maintained as a viable and functioning adipose tissue mass. The cells expressed their own basement membrane proteins consistent with the composition of adipose tissue. The ASCs could be induced to express uncoupling protein-1 (UCP-1) and cIDEA, makers of beige adipocytes with expression level varying with hydrogel stiffness. This hydrogel-based culture system serves as a first step in engineering beige adipose tissue.